2010
DOI: 10.1111/j.1365-2648.2010.05455.x
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia education programme for patients with a stoma: effectiveness evaluation

Abstract: Although further, longer-term follow-up will be useful, this study demonstrates that multimedia packages can enhance patient involvement in their stoma care and can augment stoma education - particularly in resource challenged healthcare environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 16 publications
(37 reference statements)
2
64
0
10
Order By: Relevance
“…The patients who received the guidelines with this tool improved their knowledge about selfcare, attitudes and behaviors, in a statistically significant way, when compared to those who received by the conventional way, by nurses, on the same content 18 .…”
Section: Resultsmentioning
confidence: 87%
“…The patients who received the guidelines with this tool improved their knowledge about selfcare, attitudes and behaviors, in a statistically significant way, when compared to those who received by the conventional way, by nurses, on the same content 18 .…”
Section: Resultsmentioning
confidence: 87%
“…[31] Lo et al also mentioned the effect of multimedia educational in increasing and improving knowledge of patients with a stoma about self-care services. [32,33] These results indicate that SMS-and cellphone-based applicable interventions and programs and multimedia tools can be used to improve individual health in developing countries. [33][34][35][36] The results showed a statistically significant difference in scores of knowledge and performance of mothers in both intervention groups of multimedia and SMS 1 month after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] Internationally, many authors have reported the use of VLOs for educating customers, nursing students and nurses in clinical practice about stoma. 8,13,15 There was no study in Brazil using VLOs to teach this subject, showing the need for researches of this nature.…”
Section: -8mentioning
confidence: 99%
“…[10][11][12][13][14] Internationally, many authors have reported the use of VLOs for educating customers, nursing students and nurses in clinical practice about stoma. 8,13,15 There was no study in Brazil using VLOs to teach this subject, showing the need for researches of this nature. The conduction of studies supported by guidelines for the care and treatment of people with a stoma 3,16,17 may increase the knowledge of nursing students and nurses of clinical practice on this subject, improve nursing care in the perioperative period of stoma, reduce early and late complications and encourage customer self-care.…”
Section: -8mentioning
confidence: 99%